Contribution of MicroRNAs in Chemoresistance to Cisplatin in the Top Five Deadliest Cancer: An Updated Review - Pía Loren; Nicolás Saavedra; Kathleen Saavedra; Nadine De Godoy Torso; Marília Berlofa Visacri; Patricia Moriel; Luis A. Salazar (Frontiers Media S.A., 2022)
Cisplatin (DDP) is a well-known anticancer drug used for the treatment of numerous human cancers in solid organs, including bladder, breast, cervical, head and neck squamous cell, ovarian, among others. Its most important mode of action is the DNA-platinum adducts formation, inducing DNA damage response, silencing or activating several genes to induce apoptosis; these mechanisms result in genetics and epigenetics modifications. The ability of DDP to induce tumor cell death is often challenged by the presence of anti-apoptotic regulators, leading to chemoresistance, wherein many patients who have or will develop DDP-resistance. Cancer cells resist the apoptotic effect of chemotherapy, being a problem that severely restricts the successful results of treatment for many human cancers. In the last 30 years, researchers have discovered there are several types of RNAs, and among the most important are non-coding RNAs (ncRNAs), a class of RNAs that are not involved in protein production, but they are implicated in gene expression regulation, and representing the 98% of the human genome non-translated. Some ncRNAs of great interest are long ncRNAs, circular RNAs, and microRNAs (miRs). Accumulating studies reveal that aberrant miRs expression can affect the development of chemotherapy drug resistance, by modulating the expression of relevant target proteins. Thus, identifying molecular mechanisms underlying chemoresistance development is fundamental for setting strategies to improve the prognosis of patients with different types of cancer. Therefore, this review aimed to identify and summarize miRs that modulate chemoresistance in DDP-resistant in the top five deadliest cancer, both in vitro and in vivo human models.